2021
DOI: 10.3390/su131810027
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Technology Transfer of Universities in the LINC (Leaders in Industry-University Cooperation) Program of Korea

Abstract: The purpose of our study was to propose the measures necessary to promote industry-academic cooperation by investigating and analyzing factors affecting its performance Recently, the Korean government increased the budget available for industry-academic cooperation to help nurture industrial talent and promote industry-academic cooperation. In our study, the results of industry-academic cooperation for 48 universities that carried out the 5-year LINC development project from 2012 to 2016 were analyzed via pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The findings relating to the impact of collaboration policies may be particularly useful for policymakers. For example, in South Korea, the objectives of most research support policies or national projects such as LINC (Leaders in INdustry-university Cooperation) projects applied to universities (Jin and Lee, 2021) are to improve regional competitiveness and strengthen innovation capabilities of the firms through collaboration among industry-university-research center. The analysis of this paper has, to a degree, vindicated this approach to policy design because the impact of government support for collaboration among the industry, university and institution on innovation success is positive, but only under conditions of high uncertainty (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The findings relating to the impact of collaboration policies may be particularly useful for policymakers. For example, in South Korea, the objectives of most research support policies or national projects such as LINC (Leaders in INdustry-university Cooperation) projects applied to universities (Jin and Lee, 2021) are to improve regional competitiveness and strengthen innovation capabilities of the firms through collaboration among industry-university-research center. The analysis of this paper has, to a degree, vindicated this approach to policy design because the impact of government support for collaboration among the industry, university and institution on innovation success is positive, but only under conditions of high uncertainty (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The subject factors of public service include government, economic management institutions, intermediary organizations, etc., while the subject factors of behavior include oil and gas enterprises, oil and gas industry colleges and universities offering oil and gas-related majors, and oil and gas research institutes, etc. [15].…”
Section: Internal Coupling Of Subject Factorsmentioning
confidence: 99%
“…This paper investigates all 21 GRIs related to science and technology in Korea to identify the factors that impact technology transfer performance using panel data over five years, from 2015 to 2019. In Korea, various studies have investigated the factors influencing technology transfer [42][43][44][45][46], but research on GRIs has only recently begun to draw attention [45,47], and there has been some ambiguity in the interpretation of the analysis results, as previous literature has reported that the quantitative input of organizational resources into GRIs is not proportional to their quantitative performance [48] and that GRI performance depends on the nature of the institution or its particular mission [49,50]. This may be because GRIs differ in their specific missions, but it could also be due to the budget structure, which is greatly influenced by changes in government and R & D policies.…”
Section: Hypothesesmentioning
confidence: 99%